Migração e vulnerabilidade no Seridó potiguar: uma análise do perfil do emigrante - Pedrosa, Leônidas Petrucio Dutra (2017)
The 17 cities located in the eastern and western Seridó microregions form the Seridó region of Rio Grande do Norte - RN is inserted in the northern semiarid Northeast, which is characterized by extreme climatic phenomena such as long periods of drought. In addition, historically, this area presents low rates of economic development compared to the more developed areas of the state of the RN, located in the eastern coastal range, especially those that encompass the Metropolitan Region of Natal. This situation, which combines environmental problems with poor living conditions and low human development rates, has contributed to the formation of a range of municipalities that present a population with high socio-environmental vulnerability and a low capacity to respond to long periods of water scarcity. These factors created difficulties for the development of social reproduction of its population and contributed to the wide range of individuals adopting the emigration from the region as a form of adaptation to the phenomenon. Thus, the aforementioned space presents a population dynamics that allows us to analyze, from the socioeconomic profiles of the emigrants and the non-migrant population, whether the option to migrate works as a response to the socio-environmental vulnerabilities present in this region. In this sense, in order to carry out a demographic reading of this geographic space, socioeconomic profiles such as per capita income, level of education and age of migrants and non-migrants of the region will be analyzed, since these elements are used in a wide range of research on vulnerability measurement.